Which Parameter Controls Ring Current Electron Dynamics - Haas, Bernhard; Shprits, Yuri Y.; Allison, Hayley J.; Wutzig, Michael; Wang, Dedong (Frontiers in Astronomy and Space Sciences, 2022)
Predicting the electron population of Earth's ring current during geomagnetic storms still remains a challenging task. In this work, we investigate the sensitivity of 10 keV ring current electrons to different driving processes, parameterized by the Kp index, during several moderate and intense storms. Results are validated against measurements from the Van Allen Probes satellites. Perturbing the Kp index allows us to identify the most dominant processes for moderate and intense storms respectively. We find that during moderate storms (Kp < 6) the drift velocities mostly control the behavior of low energy electrons, while loss from wave-particle interactions is the most critical parameter for quantifying the evolution of intense storms (Kp > 6). Perturbations of the Kp index used to drive the boundary conditions at GEO and set the plasmapause location only show a minimal effect on simulation results over a limited L range. It is further shown that the flux at L ~ 3 is more sensitive to changes in the Kp index compared to higher L shells, making it a good proxy for validating the source-loss balance of a ring current model.